A rare case of spontaneous ovarian hyperstimulation syndrome in a pregnant female managed conservatively - ., Shikhanshi; Chavan, Niranjan; Kapote, Deepali; Sakhalkar, Ashwini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Ovarian hyperstimulation syndrome (OHSS) is a rare syndrome, characterized by cystic enlargement of the ovaries and a fluid shift from the intravascular to the third space due to ovarian neo-angiogenesis and increased capillary permeability. It is generally iatrogenic, occurring due to administration of human chorionic gonadotrophin (hCG) during assisted reproductive techniques. Spontaneous form of OHSS is so rare that is easy to confuse the diagnosis of spontaneous OHSS with other causes. Only few cases have been reported in literature where OHSS was seen without prior stimulation from any exogenous hormones. Here we present a case of spontaneous OHSS in a 30-year-old Indian female who was 5 weeks pregnant. Since there was no history of hormone stimulation before/during this pregnancy, ovarian carcinoma instead of OHSS was thought to be the primary diagnosis. There was presence of breathlessness, ascites and bilateral ovarian masses with raised CA-125. A battery of tests and investigations, the diagnosis of moderate OHSS was made after excluding all other causes. The patient was managed conservatively and her symptoms improved with time. Ovarian hyperstimulation syndrome is generally suspected strongly in patients undergoing infertility treatment whenever there is 3rd space accumulation of fluid or increase in number of follicles in ovary. However, rarely spontaneous ovarian hyperstimulation syndrome can be considered as differential diagnosis in cases where no other causes can be found for presence of abdominal pain, nausea-vomiting, ascites, pleural effusion and enlargement of ovaries specially if the patient is pregnant. Due to increased vascular permeability in such cases along with extravascular loss of fluid, there is intravascular hypovolemia. If the diagnosis is missed, there may be risk of unnecessary interventions and morbidity in such patients. Strict monitoring of patient in hospital is required. In most cases of mild to moderate OHSS only conservative management is needed while in severe cases, intensive care unit (ICU) admission may be necessary.